ZAKAT SEBAGAI INSTRUMEN FISKAL DALAM MENUTUPI GOVERMENT EXPENDITURE DI INDONESIA - Tsaniyatul Haliyah; Ridan Muhtadi; Gancar Candra Premananto (LP2M IAI Miftahul Ulum Pamekasan, 2018)
The potential of zakat which is large in the country up to now has not been utilized by the Indonesian government to improve people's welfare. A new strategy is needed so that the potential of zakat in Indonesia can be absorbed optimally and distributed according to sharia provisions and community needs. This study aims to try to offer an idea to make zakat as an instrument of fiscal policy in Indonesia, namely to enter zakat into the posture of the Indonesian state budget, the aim of which is to optimize the absorption of zakat in the country and on its distribution target. The strategy that the authors offer to realize this is through reforming the regulatory aspects, making the structure and position of a more strategic zakat institution, namely by forming a directorate general of zakat, and entering the state budget posture zakat, namely the zakat receipt post at the receipt of non-tax revenues, and zakat expenditure posts are in the state expenditure post for poverty alleviation. Therefore, political will is needed in order to realize zakat as an instrument of fiscal policy in Indonesia.